Understanding the phenomenon of Chilean social enterprises under the lens of Kerlin's approach. Issue 2 (3rd August 2015) - Janelle A. Kerlin, Dr; Gatica, Sebastian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to contribute to the literature about the emergence of social enterprises in the world through the case of Chile by proposing the associative–business–cooperative approach as a new inclusive approach to organizational models of social enterprise that complements Kerlin's conceptual framework. Design/methodology/approach – This work included a literature review of the theoretical frameworks developed by Kerlin (2013) and Salamon and Solokowski (2010), and field work that included 20 in-depth interviews of members of the Chilean social enterprise community and three expert group discussions about the specific dynamics of Chilean social enterprises. Findings – The emergent phenomenon of social enterprise in Chile has two distinctive features that appear to indicate that Kerlin's conceptual framework does not fully capture how social enterprise is currently conceptualized in Chile: the long-term dynamics of convergence and (re-)emergence of different organizational models of social enterprises and the participation and evolution of different organizational models of social enterprise over the course of history and their lasting impact. Research limitations/implications – The lack of data is the main limitation of this research. Practical implications – Capture the emergent phenomenon of social enterprises in Chile at an early stage of development with an inclusive approach that considers the diversity of the main organizational models of social enterprise and the profound institutional changes happening in Chile during the past decades. Originality/value – A deep understanding of the Chilean institutional context in the development of social enterprises.